Signaling Specific Skills and the Labor Market of College Graduates - Matias Busso; Sebastián Monta\~no; Juan S. Mu\~noz-Morales (Institute of Labor Economics (IZA), 2023)
We use census-like data and a regression discontinuity design to study the labor market impacts of a signal provided by a government-sponsored award given to top-performing students on a nationwide college exit exam in Colombia. Students who can signal their high level of specific skills earn seven to ten percent more than identical students lacking such a signal. The signal allows workers to find jobs in more productive firms and sectors that better use their skills. The positive returns persist for up to five years. The signal favors workers from less advantaged groups who enter the market with weaker signals.
Keywords: J20; J24; J31; J44; O15; D80; 330; signaling; skills; wage returns; awards; college reputation; Colombia